AL-TAKWÄªL AL- BAá¹¬INÄª LI MUSá¹¬ALAHÄ€T AN-NAHWI (TAKAMUL AL-TASAWWUF WA AL-NAHWI) - Afandi, Zamzam; Hakim, Arief Rahman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This article intends to describe the perspective and how to interpret the Sufi perspective nahwu through the irfani epistemology which is the basis of the Sufistic knowledge system. This paper finds that the Sufis, although they accept the concepts, theories and terminologies of nahwu formulated by the experts, they provide and add a different value content than before. Nahwu which is cognitive in nature, becomes spiritual spirituality by using the takwil irfani approach which emphasizes the esoteric dimension of each reality